KORELASI KESULITAN BELAJAR DENGAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN COMPUTER NUMERICAL CONTROL (CNC) DI SMK NEGERI 12 BANDUNG - Ihwan, Nur (2014)
Abstract. CNC machining practice is one of the productive subject, in SMK Negeri 12 Bandung Machining Skills Program is crucial to improve the ability of students psychomotor aspects of being a student is competent in their field, in accordance with the needs of industry, especially the CNC machining industry, but the value for the CNC in SMK Negeri 12 Bandung is still there is not maximized because it is caused by the difficulty of learning. The purpose of this study to determine how much learning difficulties correlation with student achievement in the subjects of Computer Numerical Control (CNC) at SMK Negeri 12 Bandung and to determine which one is the dominant factor that causes learning difficulties of students in the subject of Computer Numerical Control (CNC ) at SMK Negeri 12 Bandung. The method used in this study is the use of descriptive analytic approach correlation method, this method to determine whether there is a relationship between two or more variables. Data collection is questionnaire (questionnaire) by using proportional random sample simple way by a draw without replacement, and the final value of the school (documentation). The findings in this research that there is a significant relationship between Learning Difficulties on student achievement on a CNC lathe subjects in class XI at SMK Negeri 12 PPU bandung school of year 2013/2014. For more on the cognitive ability to improve the mastery of CNC theory and improve on aspects of psychomotor (skills) in engineering practice and understand the difficulties of learning and looking for a way out.